Welcome to Americastan - Akhtar, Jabeen (London Penguin Books, 2011)
Samira, a Pakistani-American, returns home to her family in North Carolina after being dumped by her boyfriend of eight years (for her best friend), fired from her job (because she ended up in jail) and finding herself on the FBI's terror watch list (after trying to run over her ex). But living at home with her somewhat eccentric and almost-dysfunctional family proves to be both tricky and exhausting. Between learning to make aloo kofta curry, entertaining cousins from Pakistan, watching her mother spiking the punch with Captain Morgan rum, nursing her broken heart and having the Pakistani American Council foisted on her by her father, Samira cannot escape situations that are challenging, comical and, quite often, downright bizarre. Welcome to Americastan is a hilarious, delightfully irreverent yet thoughtful look at the Pakistani community in America the double lives led by the young who debate the significance of animal sacrifice while sipping cocktails; atheists who agree to having a maulvi perform their wedding just to please their parents; and parties with an open bar, but only for the goras! With effervescent humour and wit, Jabeen Akhtar turns every stereotype of Muslim Americans on its head in this quirky, refreshingly candid debut novel.
Keywords: Muslim women--Conduct of Life -- Families